Pengaruh Program Beauty Empties, Kualitas Produk, Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Di E-Commerce Soco By Sociolla Margocity Depok - Zahra Jelita Putri; Lisna Kustamtinah; Dodi Arif; Afifah Syafiiyah Afrah; Salsabila Putri Lestari (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of beauty empties programs, product quality, and service quality on purchasing decisions at the Soco by Sociolla Margocity Depok e-commerce site. Digital marketing has opened up vast business opportunities for entrepreneurs and has made it easy to expand their market reach to the online realm without being constrained by space, distance, or time. The analysis method used in this study is quantitative primary data. The tests conducted were validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, T-test, F-test, and coefficient of determination (R^2) tests. The data used in this study were collected using a questionnaire, and valid data were successfully collected from 100 respondents. The sampling method used in this study was non-probability sampling with purposive sampling technique. The testing tool used was IBM SPSS Statistics version 30. The results of this study indicate that the beauty empties program has no effect and is not significant on purchasing decisions. In addition, the two variables of product quality and service quality have a positive and significant effect on the Purchasing Decision variable. These findings provide insight that the beauty empties program does not have a positive effect, while product quality and service quality play an important role in consumer purchasing decisions.